Development of a Commercial Screed Mortar with Low OPC Content by Incorporation of Biomass Fly Ash - Marinélia N. Capela; David M. Tobaldi; Luís A. C. Tarelho; Maria P. Seabra; João A. Labrincha (Applied Sciences, 2021)
Substitute Ordinary Portland Cement (OPC) by biomass fly ash (BFA) reduce the environmental impact produced by cement-based materials, and at the same time, decreased the economic and environmental burden associated with the landfilling of this waste. This study aims to evaluate the recycling of BFA as supplementary cementitious materials (SCMs) in a commercial screed mortar formulation. Two BFA varieties, both resulting from fluidized bed combustion of forest residues, were used to replace 17, 50, and 67 wt.% of OPC. The influence of simple pre-treatment processes of the BFA, such as sieving and grinding, in the fresh and hardened state properties of the mortars, was evaluated. The BFAs were characterized in terms of chemical (XRF) and mineralogical (XRD) composition, particle size distribution (laser diffraction-COULTER) and morphology (SEM). The prepared formulations were characterized in terms of workability, mass loss upon curing, bulk density, sorptivity (by immersion and capillary), flexural and compressive strength and durability to 25 freeze–thaw cycles. Both of the BFAs are potential SCMs. Substitution of 17 wt.% OPC with BFA complied with the product technical requirements for compressive and flexural strength (10 and 3 MPa, respectively), with the ground and sieved and just sieved BFAs perform slightly better than the as-received BFA.